Traços funcionais da ictiofauna nativa determinam os traços de possíveis peixes invasores em reservatórios neotropicais - Berlatto, Amanda Frigo (2019)
1- The introduction of non-native species can cause impacts on the environment as well as negative effects on the functionality of an ecosystem. The introduced species that can establish themselves generally present life history characteristics different from the native biota and with this they can adapt easily in the altered environments. Environments modified with the formation of a reservoir generate appropriate conditions for the establishment of tolerant and opportunistic nonnative species. 2- Our study compared functional traits between native and non-native fish species in 20 reservoirs of three diferente Neotropical ecoregions in order to observe if the functional traits of the two sets of species are associated and influence the establishment of non- native. Our hypothesis was that the traits of native species significantly influence the establishment of non-native species, since the two sets of species present differences in their functional characteristics. 3- The co-inertia analysis simultaneously ordered the traits of the non-native species in relation to the native traits and the permutational test revealed that these ordinations were significantly associated (RV = 0.40, p = 0.008). This result demonstrates that the process of establishment of the non-native species is highly dependent on the characteristics of the species of the host communities. 4- According to the environmental characteristics, each reservoir presented distinct traits for the set of native and non-native species, so that the Iguaçu ecoregion was the one with the greatest functional differentiation among the species sets. 5- Therefore, our results demonstrated that the process of establishment of nonnative species is not random but highly dependent on the functional characteristics of the host assembly. The non-native species that can establish themselves are those that are successful in the competition with the native ones or by the opportunities observed when the natives do not exploit the same resources of the introduced ones.